maths homework help!!!!!! really simple steps please for someone whos really thick!!!?

please expain in simple steps

the probability that jenny will beat gill at tennis is 3/5

the probability that jenny will gill at both tennis and snooker is 1/4

what is the probability that jenny will beat gill at snooker?

Update:

please tell me how u go the answer

4 Answers

Relevance
  • Anonymous
    9 years ago
    Favorite Answer

    You have to multiply together the probabilities of Jenny beating Gill at tennis (3/5) and snooker (x) to get the probability that she'll beat him at both (1/4).

    So: 1/4 = 3/5 * x

    Rearranging:

    x= (1/4) / (3/5)

    Flip the 3/5ths so that you can multiply.

    x= 1/4 * 5/3

    Multiply across the top and and the bottom.

    x= (1*5)/(4*3)

    x= 5/12

    So the probability that Jenny will beat Gill at snooker is 5/12.

  • 9 years ago

    The probability of two things both happening is the product of the probabilities of both things happening.

    Settup the equation:

    Tennis win probability x Snooker win probability = probability of snooker and tennis win

    3/5 x S = 1/4

    3/5 x S = 1/4

    S = (1/4) / (3/5)

    S= (1/4) x (5/3)

    S= 5/12

    5/12 is the answer.

  • Anonymous
    5 years ago

    For trinomials, multiply the first term and the last term. x^2 - 12x + 36 = 0 36x^2 Compare that to the middle term. You need to find two factors of 36x^2 that add up to -12x. This is the hard part but there are clues along the way to help you through. Since the product is positive and the middle term is negative, you know both terms that you are looking for are negative. Factors of 36x^2 are -1x and -36x (no way to make that -12x). -2x and -18x (nope) -3x and -12x (nope) -4x and -9x (nope) -6x and -6x (WOOHOO!!!) Throw out the middle term and replace with the two terms that you just found. x^2 - 6x - 6x + 36 = 0 Use factoring by grouping -- group first two terms together and last two terms together. (x^2 - 6x) + (-6x + 36) = 0 Find the greatest common factor of each set. x(x - 6) + -6(x - 6) = 0 Now you have a big chunk plus another big chunk equals zero. Each chunk has (x - 6) as a common factor. Factor it out. (x - 6)(x - 6) = 0 One of those two chunks must be zero since that is the only way to get a product of zero (zero times any number is zero). If we say Chunk Number One is zero then I can write it as x - 6 = 0 and x must be 6. If Chunk Number Two is zero then I can write it as x - 6 = 0 so x must be 6. Your solution is x = 6 or 6 Hmm. That is the same thing so we can just say that x = 6. Make sure to check your work by substituting 6 into your original equation. The higher up you get in math, you will find that some answers are misleading. ALWAYS check your work!

  • T
    Lv 5
    9 years ago

    (3/5)(x) = (1/4)

    x = 5/12

Still have questions? Get your answers by asking now.